Using therapy outcome measures to identify the speech and language therapy needs of children and young people with severe acquired brain injury. (2nd December 2022) - Moll, Deborah; Edwards, Louise; Kelly, Gemma; Hamilton, Colin; Price, Helen
Abstract : Background/Aims: Children and young people often require speech and language therapy input following severe acquired brain injury. However, there is limited understanding of the impact of post-acute neurorehabilitation on children and young people's communication and swallowing, and how to measure this. The aim of this study was to evaluate the initial and ongoing speech and language therapy needs of children and young people in one specialist paediatric neurorehabilitation centre, and to determine the usefulness of therapy outcome measures for this population. Methods: A retrospective review was performed of routinely collected data, including therapy outcome measures for children and young people admitted to the centre. Descriptive analysis was completed for all therapy outcome measures data, and statistical significance of change during rehabilitation was determined on those with sufficient data using Wilcoxon signed-rank tests. Results: A total of 165 records of children and young people aged between 1 and 17 years were reviewed. The average length of stay at the centre was 19.7 weeks. The most prevalent therapy outcome measures were cognition and dysphagia. Highly significant differences were found between admission and discharge in all therapy outcome measures scores, including participation (Wilcoxon Z=-9.523, P <0.001) and wellbeing (Wilcoxon Z=-7.656, P <0.001). Median discharge scores did not exceed 4 (from a maximum of 5) for any scales. Conclusions: Therapy outcome measures were able to capture the complex profiles of these children and young people and could measure changes during post-acute neurorehabilitation. Children and young people presented with a range of speech and language therapy needs following severe acquired brain injury. They made significant improvements in impairment, activity, participation and wellbeing scales during rehabilitation. Children and young people left with ongoing speech and language therapy needs in all areas, which require input from community services.